Fiscal rules in economic crisis: The trade-off between consolidation and recovery, from a European perspective - Carmen Díaz Roldán; Fernando Ferrari Filho; Julimar Da Silva Bichara (Economics: The Open-Access, Open-Assessment Journal, 2021)
In this study, we will perform a simulation exercise to investigate whether the use of explicit fiscal rules improves the macroeconomic performance in the economic framework of the European Union (EU), where the fall in income levels occurred very asymmetrically, and this has accentuated the social inequality that existed before the recent crises. To evaluate the performance of fiscal rules, we will allow for a fiscal rule keeping the growth of the public expenditure below the growth of the inflation. This special design of the fiscal rule is a novelty in the European context, although the inflation constraint has been successfully implemented in other countries as, for example, Brazil. As the results, we expect to find that before the financial crisis of 2008, the EU public finances keep relatively stable. However, after the crisis, the budget of the member states suffered a significant deterioration. In addition, therefore, we will discuss to which extent the use of proper fiscal rules could help to rationalize fiscal consolidation efforts.
Keywords: F45; H62; H68; 330; fiscal rules; consolidation; crisis